1998
DOI: 10.1080/13556219872326
|View full text |Cite
|
Sign up to set email alerts
|

Substance misuse in Aboriginal Australians

Abstract: Australia's Aborigines lived in isolation from the rest of humanity as successful hunter-gatherers for tens of thousands of years. That isolation ended abruptly with British colonization in the late 18th century and was followed by a traumatic 200 years for Aborigines who are now seriously disadvantaged, socio-economically and in terms of their health standards. It has often been assumed that the Aborigines had no access to psychotropic substances before permanent European contact but several pieces of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
7
1
Order By: Relevance
“…5,14,15 Changed lifestyles were associated with other health risks from tobacco smoking, and the use and abuse of alcohol and other drugs, and volatile solvents and petrol. 16 It is pertinent that some of the MRR found in this study were substantially higher than recent findings from much larger jurisdictions. For example, MRR for 2012 deaths in NSW, Queensland, WA, South Australia and the Northern Territory combined were 7.0 for diabetes and 2.5 for urinary system diseases 3 compared with 19.3 and 9.9, respectively, for similar categories of causes of death in the West Kimberley in our study.…”
Section: Gracey Et Alcontrasting
confidence: 61%
See 1 more Smart Citation
“…5,14,15 Changed lifestyles were associated with other health risks from tobacco smoking, and the use and abuse of alcohol and other drugs, and volatile solvents and petrol. 16 It is pertinent that some of the MRR found in this study were substantially higher than recent findings from much larger jurisdictions. For example, MRR for 2012 deaths in NSW, Queensland, WA, South Australia and the Northern Territory combined were 7.0 for diabetes and 2.5 for urinary system diseases 3 compared with 19.3 and 9.9, respectively, for similar categories of causes of death in the West Kimberley in our study.…”
Section: Gracey Et Alcontrasting
confidence: 61%
“…This was associated with a surge in so‐called ‘lifestyle’ chronic disorders such as obesity, cardiovascular disease, hypertension, chronic kidney disease and diabetes . Changed lifestyles were associated with other health risks from tobacco smoking, and the use and abuse of alcohol and other drugs, and volatile solvents and petrol …”
Section: Discussionmentioning
confidence: 99%
“…They then either went short, became dependent on the colonisers for these essentials or obtained food by means that were considered illegal by the newcomers, such as by stealing food or killing newly introduced livestock . The new settlers also introduced harmful substances such as tobacco and alcohol, which had serious long‐term effects on health and caused severe social, psychological and emotional damage …”
Section: Impacts Of Colonisation On Indigenous Peoplesmentioning
confidence: 99%
“…3 The new settlers also introduced harmful substances such as tobacco and alcohol, which had serious long-term effects on health and caused severe social, psychological and emotional damage. 4 The fabric of traditional indigenous societies was devastated by foreign colonisers. Long-established indigenous customs and behaviours were suppressed by the imposition of alien and ill-understood regulations.…”
Section: Impacts Of Colonisation On Indigenous Peoplesmentioning
confidence: 99%
“…Despite a burgeoning body of literature on alcohol and other drug problems among Aboriginal people (for a review see Gracey, 1998), a review of Australian illicit drug research found that there has been little research into Aboriginal injecting drug use (Hando, Hall, Rutter, & Dolan, 1998). With secondary analyses of existing databases, the current study examined differences between Aboriginal and non-Aboriginal IDUs in terms of gender, prison history, hepatitis C virus antibody (HCV) testing and drug treatment history.…”
Section: Characteristics Of Aboriginalmentioning
confidence: 99%